2016
DOI: 10.1111/apt.13567
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: alginate (Gaviscon Advance) vs. placebo as add‐on therapy in reflux patients with inadequate response to a once daily proton pump inhibitor

Abstract: In patients with residual reflux symptoms despite PPI treatment, adding an alginate offers additional decrease in the burden of reflux symptoms (EudraCT/IND Number: 2011-005486-21).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 35 publications
0
56
0
9
Order By: Relevance
“…Published after our literature search, a RCT reported symptomatic improvement in PPINR at 7 days treated with adjunctive Gaviscon, an alginate formulation that forms a protective raft over the esophageal mucosa for 7 days. 69 Tegaserod is a novel prokinetic that is currently being studied as an adjunctive agent for PPINR, though the results of the trial are yet to be published. 70 Lastly, vonoprazan is a novel potassium-competitive acid blocker that has demonstrated more potent and sustained acid suppressive effects than the PPIs LAN, ESO, and RBZ.…”
Section: Discussionmentioning
confidence: 99%
“…Published after our literature search, a RCT reported symptomatic improvement in PPINR at 7 days treated with adjunctive Gaviscon, an alginate formulation that forms a protective raft over the esophageal mucosa for 7 days. 69 Tegaserod is a novel prokinetic that is currently being studied as an adjunctive agent for PPINR, though the results of the trial are yet to be published. 70 Lastly, vonoprazan is a novel potassium-competitive acid blocker that has demonstrated more potent and sustained acid suppressive effects than the PPIs LAN, ESO, and RBZ.…”
Section: Discussionmentioning
confidence: 99%
“…The number of reflux events at night also decreased remarkably with GA treatment. This study concluded that inclusion of GA in the treatment regime of patients receiving PPI therapy had further reduced the burden of reflux symptoms . Alecci et al .…”
Section: Resultsmentioning
confidence: 75%
“…Theoretically, the acid pocket would be an ideal target for this compound since alginates accumulate just below the esophagogastric junction creating a foam layer above the gastric content. Preliminary studies in patients with residual symptoms during once-daily PPI therapy have been promising: the alginate preparation as an add-on treatment to PPI was superior to placebo in reducing break-through symptoms [23]. More recent studies with larger numbers of patients have, however, produced conflicting results.…”
Section: Role Of the Acid Pocketmentioning
confidence: 99%